Pengaruh Kualitas Produk dan Harga Cat Terhadap Kepuasan Konsumen TB Adeng Jaya Kecamatan Tanjungsiang Subang - Roro Rodiah Rodiah; Jalaludin Jalaludin; Ahmad Damiri (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2019)
Based on Observations in Tanjungsiang District There are several building shops that sell paint, but the majority of people buy paint at TB Adeng Jaya because there are several kinds of paint products that are sold from paint kilos, cans, to buckets. Making it easier for consumers to buy paint in accordance with what is desired. This study aims to discuss and analyze. Effect of product quality on customer satisfaction, The effect of paint prices on customer satisfaction, as well as the influence of product quality and paint prices on customer satisfaction. The effect of paint prices on customer satisfaction, as well as the influence of product quality and paint prices on customer satisfaction. The research method used is the survey method which is sourced from primary and secondary data about the quality of product X1 and the price of paint X2 on customer satisfaction Y. seen from the purpose of this study included in the research explanatory research, because it involves 3 variables that are interconnected with each other. Based on the results of testing using SPSS 26.0 software, this study can be concluded as follows,, the effect of (X1) on (Y) has a value of Tcount 9,055> Ttable 1,988 with a significance value of 0,000 <0.05 and R square value of 0.494, this shows the quality of paint products (X1) significantly influence customer satisfaction (Y) 49.4% while the remaining 50.6% is determined by other variables, the influence of (X2) on (Y) has a T-value of 2.081> Ttable 1.988 with a significance value of 0.000 <0.05, and an R Square value of 0.049, this shows that the price of paint (X2) has a significant effect on customer satisfaction (Y) of 4.9% while the remaining 95.1% is determined by other variables,and the influence of (X1) and (X2) on (Y) has a value of F count 0.330 < Ftable 3.11 with a significance value of 0.720> 0.05, and the R square value of 0.089 does not lie in the correlation interval, this shows the quality of the product (X1) and the price of paint (X2) has no effect on customer satisfaction (Y).